Development of a power conditioner for a PMSG-based wind energy system integrated into a weak grid - Khan, Akrama (Department of Electrical Engineering, 2020)
With the growing use of non-linear loads and due to their ever changing nature, electricity networks experience power imbalance continually. These non-linear asymmetrical loads draw distorted unbalanced currents and voltages at the point of common coupling (PCC) which propagate into the distribution network. Power quality has therefore become an important issue, which has resulted in the development of numerous control strategies and other interventions to maintain the integrity of the electric network. Recent advancements in power electronics have provided new ways to optimize power systems by regulating the active power transfer. These developments lead to opportunities for renewable energy systems to harness energy and at the same time inject optimized currents into the network by means of distributed units. An emerging problem with most such units is that they are located far from the PCC and are usually designed for the small linear loads. Moreover, the problem is exacerbated during overload conditions when the voltage level drops below the allowed minimum level due to the high network impedance which characterizes a weak grid. This thesis aims to study similar scenarios where a permanent magnet synchronous generator (PMSG) based wind energy conversion system (WECS) is integrated into a weak AC grid. The system comprises of a machine-side (MSC) and a grid-side (GSC) converter, which provides available ancillary services and is envisaged to augment existing power quality conditioners such as STATCOM devices. To represent a weak grid, a Thevenin equivalent model of the electric network is considered with unbalanced loads. The main objective of this project is to transform the traditional converter topology into a versatile system that can perform as a power conditioner. In particular, it monitors a distribution line, sense changes in the load, detects faults and redistributes the currents to ensure maximized power transfer into the network. The system under consideration possesses the capability of independent injection of active and reactive currents within the defined limits. Since the system under consideration is integrated v into a weak grid, the perceived load is always considered to be unbalanced. Under the specified condition, if a fault occurs at one or two phases, unbalanced voltages are observed at the PCC. Two scenarios are created to perform the case study. Firstly, a no-fault case is considered with symmetrical voltages at the PCC. To ensure maximum power transfer into the network with least losses, a set of currents is injected according to the optimal current injection technique. Secondly, asymmetrical faults are considered at the PCC and currents are injected according to the coordinated sequence current injection technique. This technique defines a new current injection limit which not only improves the power transfer but also enhances the power factor. Furthermore, the peak magnitude of the three phase currents is also kept within the rated current limit. For both scenarios described above, the MSC regulates the DC link voltage so as to limit the active power coming from the generator according to the grid condition. The GSC however performs two important functions. It implements small active/reactive power perturbations for the impedance estimation, and once the impedances are determined, magnitudes of the required currents are calculated and injected based on the proposed techniques. Validation of the analysis is done experimentally on a 3.3kW PMSG connected to a programmable regenerative power supply which emulates a weak grid. The MSC and GSC utilized in this project are conventional two-level converters which are controlled by means of a FPGA based controller.